Bone Diagenesis and Extremes of Preservation in Forensic Science - Rhys Williams; Tim Thompson; Caroline Orr; Gillian Taylor (Humans)
Understanding the composition and diagenetic processes of the deposition environment is pivotal to understanding why bone undergoes preservation or diagenesis. This research explores the complex nexus of diagenesis at the extremes of preservation, via the interdependent chemical, and short- and long-term microbial processes that influence diagenesis. These processes include dissolution, ion exchange, hydrolysis, recrystallisation, waterlogging, acidity and alkalinity, soil composition, redox potential, bacterial activity, and microbiome composition. Diagenetic processes are discussed in relation to typical sites and sites with extremes of preservation. Understanding site conditions that impact diagenetic processes is critical to understanding the visual features presented in recovered skeletal material, ensuring an appropriate post-mortem interval is assigned, and for subsequent post hoc analysis of bone.